Sosialisasi Pemanfaatan Online Marketplace untuk Perluasan Pelanggan di Desa Sri Kuncoro Bengkulu Tengah - Azansyah azansyah; Merri Anitasari; Handoko Hadiyanto (Kreativasi : Journal of Community Empowerment, 2022)
Online marketplace provides convenience for business actors to expand their product market more cheaply and effectively. To be able to sell products in the Online marketplace, business actors need to have an account on the marketplace. Desa Sri Kuncoro, which is a developing village, needs to improve itself more quickly to achieve the status of a developed village. One way is to increase product or business sales through an Online marketplace. The purpose of this service activity is to provide a better understanding for the people of Desa Sri Kuncoro regarding the use of online market places to increase their businesses. The results of the activity stated that the Desa Sri Kuncoro Community had understanding, knowledge and skills in using the Online marketplace.